Policies affecting land management, input use and productivity: Land redistribution and tenure in the highlands of Amhara region - Benin, Samuel (International Food Policy Research Institute, 2002)
This paper presents evidence and implications of the impacts of land redistribution and land tenure contracts on land investments and management practices, input use and productivity using data from household and plot level surveys conducted in the highlands of Amhara region in 2000/01. It also examines the impacts of other policy and programme variables including education, access to infrastructure (irrigation, roads, markets), credit and extension, while controlling for many factors (including household structure and endowments, plot quality, agricultural potential population density) that may affect land management, input use and productivity. The paper ends with comments from Stein Holden.